2021
DOI: 10.3390/su13073929
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Radio Programmes in Indigenous Languages and Agricultural Productivity in North-Central Nigeria

Abstract: This study investigated the influence of agricultural radio programmes in indigenous languages on farmers’ productivity and their implications for agricultural productivity in North-Central Nigeria. It specifically explored how farmers’ knowledge of agricultural radio programmes produced in indigenous languages influences their productivity; how farmers’ acceptance of agricultural radio programmes produced in indigenous languages influences productivity; and whether behavioural changes result from agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Given our determined sample size as 405 and a random selection of five wards, a total of 81 respondents were selected from each of the ward (i.e 81∗5 = 405). However, since each ward has an average of 400–500 households ( Adekola et al., 2019 ; Adesina et al., 2018 ; Adeyeye et al., 2021 ), our sampling interval becomes 400/81(using the minimum number of household i.e 400). This resulted into a sampling interval of approximately five houses.…”
Section: Methodsmentioning
confidence: 99%
“…Given our determined sample size as 405 and a random selection of five wards, a total of 81 respondents were selected from each of the ward (i.e 81∗5 = 405). However, since each ward has an average of 400–500 households ( Adekola et al., 2019 ; Adesina et al., 2018 ; Adeyeye et al., 2021 ), our sampling interval becomes 400/81(using the minimum number of household i.e 400). This resulted into a sampling interval of approximately five houses.…”
Section: Methodsmentioning
confidence: 99%
“…Face-to-face interactions and strategies for mass mediation are all examples of this type of communication. Considering this, employing indigenous languages to communicate with agricultural communities through the media, mainly radio, fosters a sense of community among listeners [ 11 , 12 ]. Studies have shown that using the native language in radio broadcasts is the most effective way to spread mass messages since it does more with less effort than other media and is understood by the audience [ 9 , [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…insecurity in Nigeria is still a huge problem (see Figure 1), irrespective of previous ag cultural policies aimed at increasing food productivity and reducing hunger in the cou try. Various researchers opine that the inefficient farming models adopted by the sma holder farmers who constitute the largest population of farmers in Nigeria are a maj cause of perennial food insecurity [5][6][7]. Most smallholder farmers in Nigeria have be restrained to rainfed cultivation irrespective of abundant irrigable water resources sprea across a variety of agroecological zones [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the federal government launched the Agricultural Transformation Agenda in 2014 to re-engage key stakeholders in crop production of food with the Central Bank of Nigeria's (CBN) assistance through the N20 billion-naira Anchor Borrowers' Programme support for dry season irrigation farming [14][15][16], to ensure the availability of food all year round, which is a significant factor for the actualization of the Sustainable Development Goals 1 (Zero poverty), 2 (Zero Hunger), and 3 good health and wellbeing [7,17]. Thus, food security is intertwined with other SDGs.…”
Section: Introductionmentioning
confidence: 99%